1985
DOI: 10.1093/nar/13.17.6137
|View full text |Cite
|
Sign up to set email alerts
|

Altered DNA conformations detected by mung bean nuclease occur in promoter and terminator regions of supercoiled pBR322 DNA

Abstract: Mung bean nuclease was used to probe for recognizable DNA unwinding and unpairing in the plasmid pBR322. In negatively supercoiled DNA, but not relaxed DNA, cleavages occurred preferentially in non-coding regions of the genome. The types of nucleotide sequences cleaved and which non-coding regions were cleaved depended upon environmental conditions. At 37 C, cleavages occurred in an 84 bp A+T-rich sequence in the terminator region of the ampicillin-resistance gene. Recognition is likely based on a novel DNA co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
63
0

Year Published

1987
1987
1997
1997

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 81 publications
(69 citation statements)
references
References 68 publications
6
63
0
Order By: Relevance
“…When a plasmid DNA containing ARSJ in pBR322-derived vector was digested with mung bean nuclease in the absence of HSSB, the cleavage signal was strongest in the terminator region of the ampicillin resistance gene in the vector DNA and weak signals were detected in the ARS1 region. These results are in good agreement with those of Sheflin and Kowalski (43), who found that when pBR322 DNA was digested with mung bean nuclease under low ionic conditions, the terminator region of the ampicillin resistance gene was preferentially cleaved. The unwinding element in the terminator region of the ampicillin resistance gene is 84 bp long and highly A+T rich.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…When a plasmid DNA containing ARSJ in pBR322-derived vector was digested with mung bean nuclease in the absence of HSSB, the cleavage signal was strongest in the terminator region of the ampicillin resistance gene in the vector DNA and weak signals were detected in the ARS1 region. These results are in good agreement with those of Sheflin and Kowalski (43), who found that when pBR322 DNA was digested with mung bean nuclease under low ionic conditions, the terminator region of the ampicillin resistance gene was preferentially cleaved. The unwinding element in the terminator region of the ampicillin resistance gene is 84 bp long and highly A+T rich.…”
Section: Discussionsupporting
confidence: 92%
“…On the digestion of negatively supercoiled vector DNA (pBR322AEP), a pair of new bands, named band 5, appeared; these bands mapped at the 3' end of the RNA1 gene ( Fig. 4B and data not presented) (43), suggesting that the most sensitive site can be altered by the DNA context of the plasmid. In the presence of HSSB, the DNA in region 1, in addition to the DNA in region 5, was digested with the nuclease.…”
Section: Resultsmentioning
confidence: 98%
“…The removal of terminators should also identify clones in which the terminators had been increasing stability in some manner other than the prevention of read-through transcription. For example, by changing the topology of the plasmid, the hairpin structures of transcription terminators might reduce conformational changes associated with AT-rich DNA (34), which can cause deletions (14). However, we observed that when the terminators were removed, a large number of stable clones containing the expected fragment was obtained for each of the plasmids listed in Table 1, except XPL.…”
Section: Methodsmentioning
confidence: 84%
“…As described in the previous section, hot spot III in pUC118 was located in a 6-bp spacer sequence flanked by 10-bp inverted repeat sequences (Fig. 3B), which are entirely contained in the transcription terminator for bla (28). To test the possibility that the inverted repeats flanking a hot spot are responsible for preferential transposition of Tn4731, therefore, we introduced substitution mutations within each one of the inverted repeat sequences flanking hot spot III and examined transposition of Tn4731 to the resulting mutant plasmids pTT70 and pTT71 (Fig.…”
Section: Resultsmentioning
confidence: 70%